2018
DOI: 10.1194/jlr.m081745
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exploration of ACAT contributions to lipid droplet formation during adipogenesis

Abstract: As adipose tissue is the major cholesterol storage organ and most of the intracellular cholesterol is distributed to lipid droplets (LDs), cholesterol homeostasis may have a role in the regulation of adipocyte size and function. ACATs catalyze the formation of cholesteryl ester (CE) from free cholesterol to modulate the cholesterol balance. Despite the well-documented role of ACATs in hypercholesterolemia, their role in LD development during adipogenesis remains elusive. Here, we identify ACATs as regulators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
(41 reference statements)
2
28
0
Order By: Relevance
“…They are comprised of acyl-glycerols that are synthesized through the action of diacylglycerol transferases (DGATs), which convert acyl-CoA-bound fatty acids, and diacylglycerols (DAGs) into the TAGs that fill the LD core (Harris et al, 2011). Cholesterol acyltransferases synthesize CEs which are also incorporated into the core of nascent LDs (Zhu et al, 2018). Once separated from the ER membrane, LDs may continue to grow via LD fusion and further TAG incorporation.…”
Section: Lds Structure Composition and Biogenesismentioning
confidence: 99%
“…They are comprised of acyl-glycerols that are synthesized through the action of diacylglycerol transferases (DGATs), which convert acyl-CoA-bound fatty acids, and diacylglycerols (DAGs) into the TAGs that fill the LD core (Harris et al, 2011). Cholesterol acyltransferases synthesize CEs which are also incorporated into the core of nascent LDs (Zhu et al, 2018). Once separated from the ER membrane, LDs may continue to grow via LD fusion and further TAG incorporation.…”
Section: Lds Structure Composition and Biogenesismentioning
confidence: 99%
“…28 We previously demonstrated that both pharmacological inhibition of ACAT activity and ACAT knockdown resulted in decreased de novo lipogenesis and lipid droplet accumulation in cultured adipocytes. 6 To further understand the role of MBOA-1/ACAT in lipid metabolism, we investigated the effect of pharmacological inhibition of MBOA-1/ACAT on fat accumulation and fastinginduced fat mobilization in C. elegans using Avasimibe (Ava), an ACAT inhibitor developed for the treatment of cardiovascular diseases. 29 First, we examined the effect Ava on fat accumulation in high-fat C. elegans constructed by glucose administration.…”
Section: Avasimibe a Pharmacological Inhibitor Of Acat Modulates mentioning
confidence: 99%
“…in decreased de novo lipogenesis in cultured adipocytes, thereby reducing lipid droplet formation. 6 However, the physiological consequence of ACAT blockage to systemic lipid metabolism is unknown.…”
mentioning
confidence: 99%
“…Adipose tissue is the major depot for energy and cholesterol storage, with most of the intracellular cholesterol distributed in the form of lipid droplets 13,14 . Cholesterol homeostasis may have a role in the regulation of adipocyte size and function 15,16 .…”
Section: Discussionmentioning
confidence: 99%